Disruption of macrodomain protein SCO6735 increases antibiotic production in Streptomyces coelicolor - Lalić, J; Posavec Marjanović, M; Palazzo, L; Perina, D; Sabljić, I; Žaja, R; Colby, T; Pleše, B; Halasz, M; Jankevicius, G; Bucca, G; Ahel, M; et al. (American Society for Biochemistry and Molecular Biology, 2016)
ADP-ribosylation is a post-translational modification that can alter the physical and chemical properties of target proteins and controls many important cellular processes. Macrodomains are evolutionarily conserved structural domains that bind ADP-ribose derivatives and are found in proteins with diverse cellular functions. Some proteins from the macrodomain family can hydrolyze ADP-ribosylated substrates and therefore reverse this post-translational modification. Bacteria and Streptomyces, in particular, are known to utilize protein ADP-ribosylation, yet very little is known about their enzymes that synthesise and remove this modification. We have determined the crystal structure and characterized, both biochemically and functionally, the macrodomain protein SCO6735 from Streptomyces coelicolor. This protein is a member of an uncharacterised subfamily of macrodomain proteins. Its crystal structure revealed a highly conserved macrodomain fold. We showed that SCO6735 possesses the ability to hydrolyse PARP-dependent protein ADP-ribosylation. Furthermore, we showed that expression of this protein is induced upon DNA damage and that deletion of this protein in S. coelicolor increases antibiotic production. Our results provide the first insights into the molecular basis of its action and impact on Streptomyces metabolism.